INHIBITORY EFFECTS OF CRATAEGUS CURVISEPALA, SALVIA HYDRANGEA, AND BETULA PENDULA ON IN-VITRO PROTEIN GLYCOSYLATION - Sedighe Asgary; Gholam-Ali Naderi; Ahmad Movahedian Attar; Ali Sajjadian; Fateme Kafil; Zahra Fatehi (ARYA Atherosclerosis, 2010)
Abstract INTRODUCTION: Diabetes is one of the most common endocrine diseases spreading rapidly in the world. Diabetes complications are classified into acute and chronic. Non-enzymatic glycosylation of body proteins such as hemoglobin and albumin is the main cause of pathogenesis in chronic complications of diabetes. Protein glycosylation is an oxidative reaction. Antioxidants such as vitamin C may be able to reduce the chronic complications of diabetes through inhibiting protein glycosylation. The inhibitory effects of vitamin C and the polyphenolic extracts of Betula pendula, Salvia hydrangea and Crataegus curvisepala on the extent of glycosylation of albumin, insulin and hemoglobin were investigated in this study. methods: Polyphenolic extracts of the aforesaid plants were prepared at three different concentrations, namely 3.6, 1.8 and 0.9 mg/ml. Vitamin C solutions were also prepared at five concentrations, namely 0.5, 5, 10, 50 and 500 µg/ml. results: The highest degree of glycosylation inhibition of albumin and insulin was due to S. hydrangea, by 100% and 97% respectively, and that of hemoglobin was due to B. pendula by 80%. At its highest concentration, vitamin C inhibited the glycosylation of insulin, albumin and hemoglobin by 100%, 93%, and 58% respectively (P<0.05). Discussion: Based on our findings, the studied plants might be able to prevent the chronic complications of diabetes. Keywords • Polyphenolic extract • Glycosylation • Antioxidants • Albumin • Insulin • Hemoglobin • Vitamin C • Crataegus • Salvia • Betula